Effect of muscimol on cholinomimetic-induced cardiovascular responses in rats - (:unkn) unknown (ELSEVIER SCIENCE BV, 1998)
Brain acetylcholine and gamma-aminobutyric acid (GABA) are both involved in the regulation of central cardiovascular control. Despite data from anatomical and electrophysiological experiments characterizing the interaction between central GABAergic and cholinergic neurotransmission, the potential significance of this interaction in central cardiovascular regulation remains unknown. The purpose of this study was to determine whether activation of GABA(A) receptors by intracerebroventricular or intrahypothalamic administration of muscimol affects the cholinergic agonist-induced cardiovascullar responses. All experiments were performed in conscious, Sprague-Dawley rats instrumented with a guide cannula for drug injection and iliac arterial catheters for direct measurement of mean arterial pressure and heart rate. Administration of a cholinergic agonist, carbachol, either intracerebroventricularly or into the dorsomedial hypothalamic nucleus, produced a significant increase in mean arterial pressure, whereas injection of carbachol into the posterior hypothalamic nucleus caused a slight elevation in blood pressure. Pretreatment with muscimol 10 min before administration of carbachol prevented the carbachol-evoked blood pressure changes. On the other hand, carbachol produced variable changes in heart rate, depending on the site of injection. In [H-3]quinuclydinyl benzilate binding experiments, muscimol did not displace the muscarinic radioligand from its binding sites, suggesting that it does not exert any direct antagonistic activity at muscarinic receptors. These results suggest that the dorsomedial hypothalamic nucleus is a potential site of action for microinjected carbachol and that the GABAergic system has an inhibitory influence on cholinergic neurons involved in blood pressure regulation. (C) 1998 Elsevier Science B.V. All rights reserved.
Keywords: GABA; (gamma-aminobutyric); cholinergic; blood pressure; heart rate; dorsomedial hypothalamic nucleus; posterior hypothalamic nucleus; MUSCARINIC ACETYLCHOLINE-RECEPTORS; POSTERIOR HYPOTHALAMIC NUCLEUS; BLOOD-PRESSURE; BASAL FOREBRAIN; AV3V REGION; CHOLINERGIC NEURONS; GABAERGIC NEURONS; HYPERTENSION; MODULATION; CARBACHOL